Contribution to the fauna of chigger mites (Acariformes: Trombiculidae) of South Africa, with descriptions of three new genera and ten new species - Stekolnikov, Alexandr A.; Barnard, Karlien; Raubenheimer, Inge; Little, Alyssa Jade; Singo, Lola; Kipling, Jessica; Matthee, Sonja (Zootaxa, 2025)
Three new genera and ten new species of chigger mites are described from murid rodents and bush squirrels examined for parasites in South Africa: Hyracarus maximus sp. nov., H. minimus sp. nov., Walchia (Ripiaspichia) africaeaustralis sp. nov., Matiesacarus capensis gen. et sp. nov., Zumptrombicula reductiseta sp. nov., Herpetacarus (Abonnencia) oubergensis sp. nov., Rogeracarus extraordinarius gen. et sp. nov., Fynbosacarus cereris gen. et sp. nov., Helenicula eikestadensis sp. nov., and Schoutedenichia saturnia sp. nov. One new combination is established: Matiesacarus elegantissimus (Kolebinova, 1981), comb. nov. (originally in the subgenus Neotrombicula (Neotrombiculoides) Vercammen-Grandjean, 1960). Schoutedenichia nagpurensis Srivastva and Wattal, 1975, previously known from India (Maharashtra State), has been for the first time recorded in South Africa and re-described based on the new material. Two genera, Walchia Ewing, 1931 and Helenicula Audy, 1954, have been recorded in South Africa for the first time. Faunistic connections between South Africa and South and Southeast Asia are discussed.